2003
DOI: 10.1063/1.1615762
|View full text |Cite
|
Sign up to set email alerts
|

On configuration of exchanged La3+ on ZSM-5: A theoretical approach to the improvement in hydrothermal stability of La-modified ZSM-5 zeolite

Abstract: Density functional calculations have been employed to investigate the locating and binding of lanthanum cation, i.e., La͑OH) 2 ϩ , on HZSM-5 zeolite. Through geometry optimization, it was determined that lanthanum ions are favorably accommodated in the two 6-T rings of the straight channels ͑Clusters 1 and 2, see Sec. III A for details͒. Cluster 1 was found to exist in prior to Cluster 2 due to the preference of Al substitution in the T11 site ͑Cluster 1͒ rather than in the T8 site ͑Cluster 2͒. Geometry-optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
(39 reference statements)
2
21
0
Order By: Relevance
“…For example, La ions were found to retard dealumination from the zeolite and thus stabilize Co-mordenite catalysts for NO reduction [10]. In contrast, the addition of a noble metal greatly increased the resistance to water deactivation and the author suggested synergetic effect existed in the bimetallic system [14].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, La ions were found to retard dealumination from the zeolite and thus stabilize Co-mordenite catalysts for NO reduction [10]. In contrast, the addition of a noble metal greatly increased the resistance to water deactivation and the author suggested synergetic effect existed in the bimetallic system [14].…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown that addition of a second metal, such as rare earth metal La or noble metal Pd or Pt, to Co-zeolites could improve their stability in the presence of water vapor [10][11][12][13][14]. For example, La ions were found to retard dealumination from the zeolite and thus stabilize Co-mordenite catalysts for NO reduction [10].…”
Section: Introductionmentioning
confidence: 99%
“…two substituted Al sites close to each other. The 6-T rings in straight channels provide the most suitable environment for exchanged La cations, with Al situated at Al 11 site [8]. Combined with previous experimental and theoretical results [16][17][18], the same T 11 site along with a nearby T 12 site was chosen to be occupied by two Al atoms (see Fig.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…Such situation heavily restricts any improvement on the current catalyst systems. Theoretical calculations, which have been successfully applied in dealing with the interaction of zeolite-exchanged species previously [8,[11][12][13][14][15], will be attempted to resolve the above problems in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation